Peran Guru dan Pola Asuh Orang Tua dalam Membina Karakter Religius Anak Kelas 5 di MIS Muhammadiyah 01 Cibitung Wetan - Rika Damayanti; Tita Hasanah; Samsul Huda (Prodi PGMI IAI Sahid, 2023)
This study aims to determine the role of teachers and parenting styles in fostering the religious character of grade 5 children at MIS Muhammadiyah 01 Cibitung Wetan. This study used qualitative research methods. The objects in this study are parents, amounting to 6 and homeroom teachers. The data collection techniques in this study are interview techniques, observation techniques, and documentation techniques. Analysis of research data using ATLAS.ti 22 software. Based on the research results, the teacher's role in fostering religious character includes teachers as teachers and educators, teachers as advisors and assessors, teachers as mentors. All informants applied the three parenting styles, namely democratic, authoritarian, and permissive. Coaching carried out by teachers and parents on the religious character of children by guiding, supervising, and advising.